Grouper Interferon-Induced Transmembrane Protein 1 Inhibits Iridovirus and Nodavirus Replication by Regulating Virus Entry and Host Lipid Metabolism - Zhang, Ya; Wang, Liqun; Zheng, Jiaying; Huang, Liwei; Wang, Shaowen; Huang, Xiaohong; Qin, Qiwei; Huang, Youhua (Frontiers in Immunology, 2021)
Interferon-induced transmembrane proteins (IFITMs) are novel viral restriction factors which inhibit numerous virus infections by impeding viral entry into target cells. To investigate the roles of IFITMs during fish virus infection, we cloned and characterized an IFITM1 homolog from orange spotted grouper (Epinephelus coioides) (EcIFITM1) in this study. EcIFITM1 encodes a 131-amino-acid polypeptide, which shares 64 and 43% identity with Seriola dumerili and Homo sapiens, respectively. The multiple sequence alignment showed that EcIFITM1 contained five domains, including NTD (aa 1–45), IMD (aa 46–67), CIL (aa 68–93), TMD (aa 94–119), and CTD (aa 120–131). In vitro, the level of EcIFITM1 mRNA expression was significantly up-regulated in response to Singapore grouper iridovirus (SGIV), or red-spotted grouper nervous necrosis virus (RGNNV) infection. EcIFITM1 encoded a cytoplasmic protein, which was partly colocalized with early endosomes, late endosomes, and lysosomes. The ectopic expression of EcIFITM1 significantly inhibited the replication of SGIV or RGNNV, which was demonstrated by the reduced virus production, as well as the levels of viral gene transcription and protein expression. In contrast, knockdown of EcIFITM1 using small interfering RNAs (siRNAs) promoted the replication of both viruses. Notably, EcIFITM1 exerted its antiviral activity in the step of viral entry into the host cells. Furthermore, the results of non-targeted lipometabolomics showed that EcIFITM1 overexpression induced lipid metabolism remodeling in vitro. All of the detected ceramides were significantly increased following EcIFITM1 overexpression, suggesting that EcIFITM1 may suppress SGIV entry by regulating the level of ceramide in the lysosomal system. In addition, EcIFITM1 overexpression positively regulated both interferon-related molecules and ceramide synthesis-related genes. Taken together, our results demonstrated that EcIFITM1 exerted a bi-functional role, including immune regulation and lipid metabolism in response to fish virus infections.